2014
DOI: 10.1002/qj.2421
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution temperature and precipitation projections over Ontario, Canada: a coupled dynamical‐statistical approach

Abstract: We develop a dynamical–statistical downscaling approach by coupling the PRECIS regional modelling system and a statistical method—SCADS—to construct very high resolution climate projections for studying climate change impacts at local scales. The coupled approach performs very well in hindcasting the mean temperature of present‐day climate, while the performance for precipitation is relatively poor due to its high spatial variability and nonlinear nature but its spatial patterns are well captured. We then appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…PRECIS was designed with high‐resolution for both operational forecasting and atmospheric research. The regional climate model (RCM) was widely used to produce high‐resolution climate simulations (Feng et al, ; Wang et al, ; Wang, Huang, Lin, et al, ; Xu et al, ). The model's driving GCM was the Hadley Centre Global Environment Model version 2‐Earth Systems (HadGEM2‐ES), which was developed by the Met Office Hadley Centre for the Coupled Model Intercomparison Project Phase 5 (CMIP5; Collins et al, ).…”
Section: Methods and Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRECIS was designed with high‐resolution for both operational forecasting and atmospheric research. The regional climate model (RCM) was widely used to produce high‐resolution climate simulations (Feng et al, ; Wang et al, ; Wang, Huang, Lin, et al, ; Xu et al, ). The model's driving GCM was the Hadley Centre Global Environment Model version 2‐Earth Systems (HadGEM2‐ES), which was developed by the Met Office Hadley Centre for the Coupled Model Intercomparison Project Phase 5 (CMIP5; Collins et al, ).…”
Section: Methods and Data Setsmentioning
confidence: 99%
“…The chosen HadGEM2‐ES has the highest resolution among the 11 models (Jiang et al, ; Martin et al, ). In addition, previous studies have demonstrated the ability of HadGEM2‐ES to well represent most variables, especially for surface conditions and atmospheric circulation (Wang et al, ; Wang, Huang, Lin, et al, ). Overall, the HadGEM2‐ES exhibits relatively high skills in providing the lateral boundary conditions to drive the PRECIS model for high‐resolution climate change projections over China.…”
Section: Methods and Data Setsmentioning
confidence: 99%
“…Changes in climate are not expected to be uniform across the globe due to the regional variations in topography, land cover/land use, economic development and so on (Hamilton and Keim, 2009;Paeth et al, 2009;Jordan et al, 2014;Wang et al, 2014a), implying that the subsequent consequences caused by climatic changes will not be equally distributed. Investigating the regional effects of global warming is thus of great concern for decision makers and resources managers to help develop scientifically informed policies and strategies against the changing climate (Alexander and Arblaster, 2009;Liepert and Previdi, 2009;Stott et al, 2010;Wang et al, 2013;Wang et al, 2014c;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, RCMs are developed using the same laws of physics as described in GCMs to account for the sub-GCM grid scale processes with more regional details (such as mountain ranges, coastal zones, inland waters, and details of soil properties) in a physically-based way (Feser et al 2011). By nesting RCMs into GCMs, dynamical downscaling can be used to develop the improved simulation of the local climate system with provision of a large number of climate variables at fine spatial scales, and is thus increasingly attracting the attention of climate impact researchers in recent years (e.g., Caldwell et al 2009;Castro et al 2005;Chan et al 2014;Fujihara et al 2008;Gao et al 2013;Gao and Giorgi 2008;Kanamitsu et al 2010;Nobre et al 2001;Rockel et al 2008;Sánchez et al 2004;Wang et al 2014b). …”
mentioning
confidence: 99%
“…With the advancement of numerical modeling and simulation, global climate models (GCMs) has been widely used to project future climate under different emission scenarios (Nakicenovic 2000;Van Vuuren et al 2011). Because the spatial resolution of GCM outputs is typically too coarse for regional impact studies, further downscaling is required for deriving regional climate details from the coarse-resolution outputs (Giorgi et al 1993a, b;Maurer et al 2007;Wang et al 2014b). Downscaling techniques are usually classified into two categories: (1) dynamical downscaling through nesting fine-resolution regional climate models (RCMs) into GCMs, and (2) statistical downscaling involving the development of quantitative relationships between large-scale atmospheric variables and local weather variables such as temperature and precipitation (Hewitson and Crane 1996;Wilby and Wigley 1997).…”
mentioning
confidence: 99%